Macrophages During the Fibrotic Process: M2 as Friend and Foe - Braga, Tarcio Teodoro; Agudelo, Juan Sebastian Henao; Camara, Niels Olsen Saraiva (Frontiers in Immunology, 2015)
Macrophages play essential activities in homeostasis maintenance, tissue regeneration and wound healing. However, when the physiological process of wound healing is deregulated by persistent insults and chronic diseases, macrophages can participate actively in the development of fibrosis. In this regard, the exacerbation or resolution of fibrosis depends on the type of macrophages polarized and the severity and duration of the inflammatory insult. M1 macrophages use glycolytic metabolism to optimize oxygen consumption and activate myofibroblasts and fibrocytes. On the other hand, M2 macrophages, which use oxidative metabolism, have anti-inflammatory properties due to their capacity to produce and secrete IL-10, TGFβ and arginase that promotes tissue repair. However, when the primary insult is not controlled and there is a persistent M2 macrophage activity, these cells promote ECM deposition through the continuous production of TGFβ and growth factors. In this scenario, M2 macrophages act as a break point between normal wound healing and the pro-fibrotic process. Here, we review the aspects of tissue repair based on macrophage biology and we evidence scar formation is directly related to the degree of inflammation, but also with the appearance of M2 macrophages.